2018
DOI: 10.3389/fphys.2018.00993
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stress Directional Abnormalities in BAV Aortas: Toward a New Hemodynamic Predictor of Aortopathy?

Abstract: The bicuspid aortic valve (BAV) generates wall shear stress (WSS) abnormalities in the ascending aorta (AA) that may be responsible for the high prevalence of aortopathy in BAV patients. While previous studies have analyzed the magnitude and oscillatory characteristics of the total or streamwise WSS in BAV AAs, the assessment of the circumferential component is lacking despite its expected significance in this highly helical flow environment. This gap may have hampered the identification of a robust hemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The pathophysiological process leading to the medial layer remodeling in the case of BAV is poorly understood. Two assumptions have been formulated and are not necessarily conflicting: on the one hand, a constitutive aortic wall alteration due to genetic predisposition, on the other hand an acquired aortic wall alteration due to the modified amplitude and direction of the flow wall shear stress, generated by the BAV (Girdauskas et al, 2011; Sievers and Sievers, 2011; Piatti et al, 2017; Liu et al, 2018). The presence of matrix degeneration is thus emphasized in areas with high shear stress (Gore and Seiwert, 1952; Gosline et al, 2002).…”
Section: Structural Changesmentioning
confidence: 99%
“…The pathophysiological process leading to the medial layer remodeling in the case of BAV is poorly understood. Two assumptions have been formulated and are not necessarily conflicting: on the one hand, a constitutive aortic wall alteration due to genetic predisposition, on the other hand an acquired aortic wall alteration due to the modified amplitude and direction of the flow wall shear stress, generated by the BAV (Girdauskas et al, 2011; Sievers and Sievers, 2011; Piatti et al, 2017; Liu et al, 2018). The presence of matrix degeneration is thus emphasized in areas with high shear stress (Gore and Seiwert, 1952; Gosline et al, 2002).…”
Section: Structural Changesmentioning
confidence: 99%
“…A correlation was further observed between the distal ascending aorta diameter in BAV patients with fusion of the right and non-coronary cusps (RN-BAV) but not in BAV patients with fusion of the right and left coronary cusps (RL-BAV) (Youssefi et al, 2017 ; Raghav et al, 2018 ). Flow displacement correlates with both type 1 aortopathy (involvement of the aortic root) and type 3 aortopathy (distal ascending aorta) which are more common in RN-BAV, whereas type 2 aortopathy (mid-ascending aorta) is more common in RL-BAV (Della Corte et al, 2012 ; Della Corte, 2014 ; Mahadevia et al, 2014b ) as confirmed by Liu et al ( 2018 ). In the current study the WSS data are not directly correlated to histopathologic investigation of the aortic tissue.…”
mentioning
confidence: 71%
“…We read with interest the study by Liu and coworkers in which they have addressed the role of hemodynamics in the development of aortopathy in bicuspid aortic valve (BAV) patients (Liu et al, 2018 ). BAV is the most common congenital cardiac malformation, with a prevalence of 1–2% in the general population (Michelena et al, 2015 ).…”
mentioning
confidence: 99%
“…Although our candidate DMRs showed no significant correlation with several histological markers associated with elastin degradation and dysregulation of ECM proteins known to occur in aortopathy, the integrity of the aortic wall is impacted by many factors, including apoptosis that leads to the depletion of vascular smooth muscle cells. [32][33][34] Regardless of the mechanism of cell death, DNA fragmentation and its release into the circulation is a common endpoint. Thus, the level of aortaspecific cfDNA is potentially an independent and end-stage measure of aortic cell death, regardless of mechanism.…”
Section: Discussionmentioning
confidence: 99%